Alla ricerca dell'identità dell'apostolo Paolo - Bianchini, Francesco (Rivista biblica, 2009)
This study on the identity of Paul sets up a comparison between two different perspectives: "Paul according to others" and "Paul according to Paul". It turns out that the recent heightened interest that scholars have shown in the Jewish identity of the apostle is justified, for he himself emphasises this element in his own self-presentation. At the same time, it is necessary today to deepen our knowledge of the literary and discursive models of Paul's Greek and Roman culture in order to comprehend his mode of reasoning and, now that prejudiced confessional readings have been abandoned, to understand the relationship between him and the primitive Church. In sum, the search for a unifying factor in the complex Pauline identity is answered not only by the witness of Acts but also that of the apostle himself as an evangelist of that Christ who changed his life once for all as he states in 1Cor 9:19-23